Effects of Comparison of Feed Composition, pH, and Preliminary Treatment of Biogas Production from Cow Blood Waste and Molasses - Budiyono Budiyono; Ichwanul Muttaqin; Renyka Dwi Febriatiningrum; Hashfi Hawali Abdul Matin (Diponegoro University, 2021)
Energy problems in Indonesia are issues that are not easy to solve. If the energy needs dominated by BBM continue to increase without any changes in the pattern of energy use, then Indonesia's sustainability and energy security will be disrupted. Therefore, Indonesia really needs alternative energy. Biogas is an alternative energy produced from the anaerobic degradation of organic compounds and can be a substitute for natural gas and fossil fuels. Cow's blood which is a waste from slaughterhouses can be used as a substrate for anaerobic biogas production by rumen and molasses. The objectives of this study are (i) To examine the comparison of the concentration of blood and molasses added to the volume of biogas produced, (ii) To examine the effect of pasteurization on blood on the volume of biogas produced, (iii) To examine the effect of initial system pH regulation on the volume of biogas produced, (iv) Assessing the pH setting and without adjusting the pH after measuring the volume of biogas produced. This research was conducted by making variations in the composition of feeds, pH stabilization, and blood pasteurization. The process of biogas formation is carried out for 40 days at room temperature with the response of quantitative results in the form of biogas volume every 2 days. Biogas production in cow's blood gets the best results at C/N 30, using pH 8. Pretreatment of blood pasteurization and pH stabilization also shows the best biogas results.